Financial Inclusion and Growth of Women Led SME in Mukono Municipality - Aidah Nakayobyo (My University, 2024)
The concept of financial inclusion refers to a situation where all people have the opportunity to access and utilize appropriate formal financial services. Financial inclusion is a crucial factor in economic development and poverty eradication. In Uganda, as with most Sub –Sahara African countries, SMEs form a very important strand in the economy, especially in bringing about employment and income generation. Concretely, the objectives of this study are, To determine the ease of access to financial services by women-led SMEs in Mukono Municipality by the end of the study. To determine what the key issues are that facing the women-led SMEs in Mukono Municipality in accesses to financial services within six months. To recommend at least three feasible ways through which financial access for women-led SMEs can be improved in Mukono Municipality and have them implemented within one year. This study tries to establish the level at which financial services are accessible to women-led SMEs in Mukono Municipality. What is the relationship between the interest rate and growth of women SMEs? To show the relationship between credit policy and growth of women led SMEs in Mukono municipality. This study evidences that financial inclusion is an important factor in the growth of the Women-Led SMEs in Mukono Municipality. Although the majority of women entrepreneurs pursue active inclusion in finance, the actual access to resources by most of these women poses quite significant barriers. Removing such obstacles and improving financial literacy will definitely help to achieve the two-fold objective: empowering women entrepreneurs and making the entrepreneurship environment more inclusive.